Body and Corporality in adolescents and young adults with spinal cord injury - Diana Milena; Yuri Marcela; María Elisa (Investigación y Educación en Enfermería, 2016)
Objective. To describe the meaning given by adolescents and young adults to the changes in their bodies and corporality after a spinal cord injury. Methods. Qualitative study based on symbolic interactionism in which 12 adolescents and young adults, who had suffered spinal cord injury 6 months or more before, participated. The information was recollected through a series of in-depth interviews and field journals. The guidelines proposed by Corbin and Strauss were followed for the process of codification and categorization of the data. Results. Four categories were identified that describe the meanings given by participants to the changes in their bodies and corporality: Transformation of self-image, living with contradictions in the relationships with others, withstanding the burden of a disability and adapting to the new conditions. Conclusion. The results allow for the comprehension of the meanings that are given by the people who have suffered a spinal cord lesion to their situation. This will in turn open the possibility of offering these people a better individual nursing care that focuses more on the particular needs, so that both they and their families can be helped on their way to adaptation to the new situation. How to cite this article: Duarte DM, Torres YM, Moreno ME. Body and Corporality in adolescents and young adults with traumatic lesions of the spinal cord. Invest Educ Enferm. 2016; 34(1): 84-93